Effect of Surgical Margin Width on Patterns of Recurrence among Patients Undergoing R0 Hepatectomy for T1 Hepatocellular Carcinoma: an International Multi-Institutional Analysis - Tsilimigras, D (2020)
Introduction: Although a positive surgical margin is a known prognostic factor for recurrence, the optimal surgical margin width in the context of an R0 resection for early-stage hepatocellular carcinoma (HCC) is still debated. The aim of the current study was to examine the impact of wide (> 1 cm) versus narrow (< 1 cm) surgical margin status on the incidence and recurrence patterns among patients with T1 HCC undergoing an R0 hepatectomy. Methods: Between 1998 and 2017, patients with T1 HCC who underwent R0 hepatectomy for stage T1 HCC were identified using an international multi-institutional database. Recurrence-free survival (RFS) was estimated, and recurrence patterns were examined based on whether patients had a wide versus narrow resection margins. Results: Among 404 patients, median patient age was 66 years (IQR: 58-73). Most patients (n = 326, 80.7%) had surgical margin < 1 cm, while 78 (19.3%) patients had a > 1 cm margin. The majority of patients had early recurrences (< 24 months) in both margin width groups (< 1 cm: 70.3% vs > 1 cm: 85.7%, p = 0.141); recurrence site was mostly intrahepatic (< 1 cm: 77% vs > 1 cm: 61.9%, p = 0.169). The 1-, 3-, and 5-year RFS among patients with margin < 1 cm were 77%, 48.9%, and 35.3% versus 81.7%, 65.8%, and 60.7% for patients with margin > 1 cm, respectively (p = 0.02). Among patients undergoing anatomic resection, resection margin did not impact RFS (3-year RFS: < 1 cm: 49.2% vs > 1 cm: 58.9%, p = 0.169), whereas in the non-anatomic resection group, margin width > 1 cm was associated with a better 3-year RFS compared to margin < 1 cm (86.7% vs 47.3%, p = 0.017). On multivariable analysis, margin > 1 cm remained protective against recurrence (HR = 0.50, 95%CI 0.28-0.89), whereas Child-Pugh B (HR = 2.13, 95%CI 1.09-4.15), AFP > 20 ng/mL (HR = 1.71, 95%CI 1.18-2.48), and presence of microscopic lymphovascular invasion (HR = 1.48, 95%CI 1.01-2.18) were associated with a higher hazard of recurrence. Conclusion: Resection margins > 1 cm predicted better RFS among patients undergoing R0 hepatectomy for T1 HCC, especially small (< 5 cm) HCC. Although resection margin width did not influence outcomes after anatomic resection, wider margins were more important among patients undergoing non-anatomic liver resections.